Challenge and perspective for Digital Silk Road - Bora LY (Taylor & Francis Group, 2020)
A Digital Silk Road (DSR) strategy is increasing within the BRI since countries are expected to collaborate on emerging technology for development and trade. Digital connectivity and evolving digital economies, as can be seen in China and some BRI countries, can have a positive effect on growth. However, there are some complexities and risks to DSR arising from the fact that the declared ambitions in the Chinese state differ drastically from the elusive existence of active Chinese participation, particularly in terms of the digital aspect of the strategy. The purpose of this paper is to analyze the perspectives and challenges for DSR, and the implication of BRI goes digital. Drawing from Nethpolitik and Liberal lens, this paper offers a broad overview of the communication and information segment of the initiative, which has so far been undervalued or even overlooked in the existing literature. The study asserts that DSR will broaden economic transition, strengthen regional integration, and support financial sources to boost global multilateralism and political stability. Accordingly, some risks cannot be ignored for DSR, such as political, ideology, data, and privacy hazards.